Tuan Guru Batak: A Phenomenon of Religion, Culture and Practical Politics - Muary, Rholand; Nurwahyu, Ardi (Master Program of Sociology, Universitas Malikussaleh,, 2024)
The democratic party not only provides a stage for political maneuvering by the political elite, but also the role of cultural clerics. The cultural cleric is Tuan Guru Batak (TGB) Ahmad Sabban Rajagukguk who is the leader of the Naqsyabandiyah Order in Simalungun. The purpose of this research is to find out the involvement of Tuan Guru Batak in the practical politics of the 2020 Medan City Election. Using qualitative research methods with data collection techniques through observation, interviews, and literature studies. The results of this study show that Mr. Batak's involvement in politics is practically based on the desire to spread networks and gain legitimacy from power. Conclusion in this study, Tuan Guru Batak built political relations to become a ruling partner in strengthening the position of the Naqshbandiyah Order in society in the context of religion and nationality.